Study of the Significance of Thromboelastography Changes in Patients with Dyslipidemia - Qing Lin; Guokai Yang; Jingming Ruan; Peng Yu; Chaochao Deng; Weitao Pan (Emergency Medicine International)
Purpose. To investigate the changes in thromboelastography (TEG) in patients with dyslipidemia to study its effect on the blood coagulation status. Methods. 131 patients hospitalized in Fujian Provincial Jinshan Hospital from January 2018 to December 2020 were selected, and 64 cases in the hyperlipidemia (HL) group and 67 cases in the non-HL group were set according to whether their blood lipids were abnormal. By measuring the changes of each parameter of TEG in patients, the relevant parameters R value, K value, α angle, and MA value were calculated. And routine blood coagulation (PT, APTT, INR, FIB, and TT) and routine blood (platelet count) tests were performed on all study subjects to analyze the changes of each index of the coagulation function and each parameter of TED in both groups and explore the clinical value of TEG on HL diseases. Results. Compared with the non-HL group, R and K values decreased, and angle and MA values increased in the HL group (P<0.05). PT, APTT, and INR values decreased, and FIB values increased in the HL group compared with the nonhyperlipidemic group (P<0.05). The TT levels were similar in the non-HL group and the HL group (P>0.05). Compared with the non-HL group, PLT values decreased, and PDW and MPV values increased in the HL group (P<0.05). R value was positively correlated with APTT, r= 0.373, P=0.002. K value was negatively correlated with PLT, r= −0.399, P=0.002. α angle and MA values were positively correlated with PLT, r= 0.319/0.475, P=0.010/P<0.001. The rest of the indexes did not correlate with each parameter of TEG significant correlation. Conclusion. TEG can predict the hypercoagulability and hypocoagulability of blood by the changes of R value, K value, α angle, and MA to evaluate the effect of hyperlipidemia on the coagulation status, which is important for guiding the adjustment of lipid-lowering, antithrombotic, and anticoagulation programs in patients with atherosclerosis combined with hyperlipidemia or postsurgery combined with hyperlipidemia.